INTEGRATED WASTE PROCESSING OF METALLURGICAL AND COAL BENEFICIATION PRODUCTION USING SMALL BLAST FURNACES - SMIRNOV, OLEKSIY; KUKHAR, VOLODYMYR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
This article examines the application of small blast furnaces (SBFs) for the integrated processing of metallurgical and coal beneficiation wastes. SBFs provide a cost-effective solution for pig iron production by utilizing carbon-containing pellets derived from metallurgical sludge and coal beneficiation residues. A key technological advantage lies in the production of unfired pellets, which eliminates the need for additional fuel consumption and significantly reduces energy costs. The research highlights the complete utilization of blast furnace gas within the complex, using it not only for the ironmaking process but also for electricity generation. This enables the furnace to operate with minimal reliance on external energy sources. The modular design of these furnaces allows for relocation to regions where waste supply is abundant, extending the furnace's operational lifespan. With a processing capacity of up to 200,000 tons of metallurgical waste and 40,000 tons of coal waste annually, these complexes are well-suited for regions with accumulated waste materials. However, the research identifies several challenges, including the variability in the composition of iron-containing wastes, particularly during winter months, which affects furnace performance. Addressing these issues requires the development of more consistent waste preparation processes tailored to the specific region's waste composition. The article concludes that with improved waste management and preparation, SBFs can ensure stable operation and continue to provide sustainable solutions for waste processing in the metallurgical sector for 15…20 years, supporting both cost-efficiency and environmental benefits.
Keywords: small blast furnaces; metallurgical waste processing; carbon-containing pellets; energy-efficient technologies; integrated waste processing; blast furnace gas utilization